Follicular Helper T Cells in the Immunopathogenesis of SARS-CoV-2 Infection - Cui, Dawei; Tang, Yuan; Jiang, Qi; Jiang, Daixi; Zhang, Yun; Lv, Yan; Xu, Dandan; Wu, Jian; Xie, Jue; Wen, Chengping; Lu, Liwei (Frontiers in Immunology, 2021)
Coronavirus disease 2019 (COVID-19), caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a serious infectious disease that has led to a global pandemic with high morbidity and mortality. High-affinity neutralizing antibody is important for controlling infection, which is closely regulated by follicular helper T (Tfh) cells. Tfh cells play a central role in promoting germinal center reactions and driving cognate B cell differentiation for antibody secretion. Available studies indicate a close relationship between virus-specific Tfh cell-mediated immunity and SARS-CoV-2 infection progression. Although several lines of evidence have suggested that Tfh cells contribute to the control of SARS-CoV-2 infection by eliciting neutralizing antibody productions, further studies are needed to elucidate Tfh-mediated effector mechanisms in anti-SARS-CoV-2 immunity. Here, we summarize the functional features and roles of virus-specific Tfh cells in the immunopathogenesis of SARS-CoV-2 infection and in COVID-19 vaccines, and highlight the potential of targeting Tfh cells as therapeutic strategy against SARS-CoV-2 infection.